1995
DOI: 10.1002/ajp.1350370302
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal weight in gibbons (Hylobates spp.)

Abstract: Neonatal and birth weights of gibbons have mostly been reported for single individuals, and larger samples (n = 2-8) have apparently been published for only two species of gibbons (Hylobates lar and H . syndactylus). In addition, a critical examination of the few published neonatal weights of gibbons shows that several of them should not be used. Neonatal weights are here defined as weights taken on infants up to seven days old, whereas birth weights include only those taken on the day of birth. This paper pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…For this reason, in the present study we used only a simplified classification at the superfamily level. For additional information regarding the taxonomic status of the species mentioned in this paper see, for example, Napier and Napier (1972), Corbet and Hill (1980), Mittermeier et al (1992), Rylands et al (1993), Snowdon (1993), Groves (1993) and Geissmann (1994).…”
Section: Animalsmentioning
confidence: 99%
“…For this reason, in the present study we used only a simplified classification at the superfamily level. For additional information regarding the taxonomic status of the species mentioned in this paper see, for example, Napier and Napier (1972), Corbet and Hill (1980), Mittermeier et al (1992), Rylands et al (1993), Snowdon (1993), Groves (1993) and Geissmann (1994).…”
Section: Animalsmentioning
confidence: 99%
“…T t is the proportion of adult time spent carrying the infant during travel at time t. The mass of infants of each age was estimated using a body mass at birth of 540 gm (Geissmann and Orgeldinger, 1995) and a growth rate of 4.9 gm/day (Leigh and Shea, 1995). A previous study of infant-carrying in baboons suggested that the costs of infant-carrying may be more sensitive to the distance traveled than the time spent traveling (Altmann and Samuels, 1992).…”
Section: Estimation Of the Costs Of Infant-carryingmentioning
confidence: 99%
“…Because of their dense rainforest habitat, gibbons are difficult to study in the wild, and so only a limited amount of research has been done [Dallmann and Geissmann, 2001;Geissmann and Nijman, 2006;Nijman, 2004]. Data on the reproductive biology of the species are largely nonexistent [Kappeler, 1984;Geissmann and Orgeldinger, 1995;Geissmann, 1991], and many important lifehistory factors, such as age at sexual maturity, interbirth interval, and ovarian cycle lengths, have only been estimated [Geissmann, 1991].…”
Section: Introductionmentioning
confidence: 99%